Educational Technology and Principles and Methods of Teaching English - Ali Ashrafi (Indonesian Journal Of Educational Research and Review, 2021)
The use of various audio-visual technologies in the teaching and learning process is very important. However, one of the most important teacher skills and knowledge is familiarity with this technology in English. The purpose of this study was to analyze the instructive innovation in the form of utilizing PC assets in learning English. The current investigation was led using enlightenment strategies accumulated by library procedures, which were collected taking into account educational innovations, related issues, articles, and books which have been referenced in the references. The results of this study show that encouraging guides as interfaces have options to do their job well. It would be better if the instructor had basic skills to use this device. Due to the problems of our nation's learning system in displaying English and the lack of trained students' skills, especially in speaking, listening, and writing, many guardians are trying to make up for this deficiency in the learning system by turning to state-of-the-art schools. Therefore, in this article, we have chosen to analyze the task of encouraging progress of assistance in promoting the teaching of English in the homeroom. So, it can be concluded that the use of PC resources, as well as e-learning, can help teachers in the classroom and remember that it enhances training ideas and makes students excited to learn.